Consumption of whole grains in French children, adolescents and adults - Bellisle, France (Br J Nutr, 2014)
The consumption of whole grain foods is associated with many nutritional, health and weight control benefits. The present study assessed whole grain intake in France on the basis of a 7 d dietary survey in a representative sample of children, adolescents and adults (Comportements et Consommations Alimentaires en France 2010 survey). Special care was taken to identify and assess the intake of all whole grains. All foods consumed were considered, with no lower limit on whole grain content. For the majority of foods, details regarding the whole grain contents were obtained from brand information and quantitative nutrient declarations on food labels. Over half of the respondents reported never consuming any whole grain. In participants who did, consumption levels were very low (about 9·1 g/d in children and 14·4 g/d in adults). The main food sources of whole grains were breakfast cereals in children and adolescents and bread in adults. Consumers of whole grains had higher daily intakes of fibre and several vitamins and minerals than non-consumers. In adults but not in children, the OR for overweight/obesity decreased significantly as the level of whole grain consumption increased. Although a majority of French consumers comply with the national recommendation to consume a starchy food with each meal, they do so with minimal consumption of whole grain foods.